Central pontine myelinolysis in liver transplantation. Issue 11 (November 1991) - Boon, A P; Carey, M P; Adams, D H; Buckels, J; McMaster, P
Abstract : Five cases of central pontine myelinolysis (CPM) were detected by neuropathological examination in a series of 50 patients coming to necropsy after liver transplantation. One patient also had extrapontine myelinolysis. In no case was the diagnosis made during life. Only two patients showed rapid rises in serum sodium concentrations. The incidence of hyponatraemia, before and after transplantation, and rapid rises in serum sodium in patients with CPM was significantly greater than in the 45 patients showing no neuropathological evidence of CPM. It is concluded that there is a high incidence of CPM after liver transplantation, that clinical diagnosis is difficult, and that there is no simple direct correlation between rapid serum sodium changes and the development of this condition. Avoidance of major electrolyte fluctuations at the time of liver transplantation is recommended but it must be emphasised that CPM may occur without any rapid rise in serum sodium concentration.